2019
DOI: 10.1177/2332858419887736
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Engagement Shifts Among At-Risk High School Students Enrolled in Online Courses

Abstract: Academic behaviors such as attendance are highly associated with academic outcomes. High schools are also increasingly turning to online courses to educate their most marginalized students. In this study, I explored the extent to which enrollment in an online course improved engagement and allowed students to make course progress online outside the traditional school day by examining within-student changes in academic behaviors. Students completed their online course in fewer class periods than required to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…To better understand the factors that influence high school students' engagement in online learning, researchers have conducted a series of studies. Some studies have shown that in an online learning environments, high school students' behaviour is a prerequisite for learning engagement (Darling-Aduana, 2019). However, a recent study found that high school students' cognitive and emotional engagement in online learning is suppressed by the lack of emotion, equipment, and resources in the online learning environment, and by ineffective online learning experiences (Chiu, 2021b).…”
Section: Online Learning Engagement and Regulatory Focusmentioning
confidence: 99%
“…To better understand the factors that influence high school students' engagement in online learning, researchers have conducted a series of studies. Some studies have shown that in an online learning environments, high school students' behaviour is a prerequisite for learning engagement (Darling-Aduana, 2019). However, a recent study found that high school students' cognitive and emotional engagement in online learning is suppressed by the lack of emotion, equipment, and resources in the online learning environment, and by ineffective online learning experiences (Chiu, 2021b).…”
Section: Online Learning Engagement and Regulatory Focusmentioning
confidence: 99%
“…At the same time, another body of work showed that online learning helped highly motivated students with high intellectual abilities to expand their knowledge when online learning was used in addition to traditional methods (Heppen et al, 2017). Those students who learned using a blended approach, in which online resources complement, but do not replace, traditional education, showed almost the same high results as those who learned in a traditional format (Escueta et al, 2017;Darling-Aduana, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…These findings suggest that virtual learning as implemented during the fall of 2020 in the district studied might be most viable as an alternative learning mode for students identified as female and/or belonging to historically advantaged groups. In turn, this might allow for spillover benefits for students who remain in a more comprehensive, traditional, face-to-face instructional environment (Darling-Aduana, 2019; Hart et al, 2019). Further, continuing to offer virtual learning where feasible might be a helpful option to provide students likely to benefit from anytime, anywhere access (i.e., students who possess sufficient self-regulation skills and/or out-of-school resources to monitor their own engagement), so long as schools are able to also implement fidelity and quality-control measures to accurately measure and foster engagement (Darling-Aduana, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…George et al, 2021). Additionally, continuing virtual-learning options for some students might result in spillover benefits for students who remain in face-to-face classrooms (Darling-Aduana, 2019; Hart et al, 2019). As virtual learning is likely to play an increased role in students’ educational experiences in coming school years, continued study is merited to identify how to most effectively leverage virtual learning to achieve the goals of enhancing the educational experiences of all students, with an eye toward minimizing existing educational opportunity gaps.…”
Section: Equity In Virtual Learning Before During and After The Covid...mentioning
confidence: 99%